2022
DOI: 10.1021/acsomega.2c00305
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of the Interaction with Gram-Negative and Gram-Positive Bacteria of Hydrothermal Carbon Nanoparticles Associated with Bac8c2,5Leu Antimicrobial Peptide

Abstract: Antimicrobial peptides (AMPs) are widely studied as therapeutic agents due to their broad-spectrum efficacy against infections. However, their clinical use is hampered by the low in vivo bioavailability and systemic toxicity. Such limitations might be overcome by using appropriate drug delivery systems. Here, the preparation of a drug delivery system (DDS) by physical conjugation of an arginine-rich peptide and hydrothermal carbon nanoparticles (CNPs) has been explored, and its antimicrobial efficacy against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, they do not explain the observed higher activity of the largest LCNP with respect to both the soluble copper and SCNP. In a previous study [66], we showed that CNPs strongly interact with E. coli and S. aureus by forming aggregates that might favor the transport of the loaded antimicrobial agents close to the bacterial cells. A similar effect might account for the higher bioactivity of LCNP-Cu; in fact, since the experiments were performed with equal concentrations of copper, the available surface for interactions with bacteria was 10 time higher for LCNP-Cu than with SCNP-Cu.…”
Section: Assessment Of the Release Of Copper Ions In Food Simulantsmentioning
confidence: 91%
“…However, they do not explain the observed higher activity of the largest LCNP with respect to both the soluble copper and SCNP. In a previous study [66], we showed that CNPs strongly interact with E. coli and S. aureus by forming aggregates that might favor the transport of the loaded antimicrobial agents close to the bacterial cells. A similar effect might account for the higher bioactivity of LCNP-Cu; in fact, since the experiments were performed with equal concentrations of copper, the available surface for interactions with bacteria was 10 time higher for LCNP-Cu than with SCNP-Cu.…”
Section: Assessment Of the Release Of Copper Ions In Food Simulantsmentioning
confidence: 91%
“…112 Other important advantages of HCNPs are their biocompatibility. In fact, they exhibit low toxicity against the cells of the immune system and act as antioxidants 113 and are hemo compatible. 114 In addition, previous data suggest that HCNPs are slowly degraded by neutrophils.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Nowadays, the most widely used techniques in the synthesis of the nanoparticle are chemical methods and biological methods. Te most common chemical methods such as vapor deposition, sol-gel, thermal evaporation, microwave-assisted, pulsed laser deposition, electrochemical reaction, sputtering, hydrothermal, solvothermal, and microemulsion are used in the fabrication of nanoparticles [41][42][43][44]. Similarly, Co 3 O 4 @ZnO core-shell NPs have been synthesized by using the chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%